(untitled) (Pharmacy Essentials: A Compact Guide for Students and Practitioners, 2025)
Author Miss Farsiya Fatima, Associate Professor, Department of Pharmaceutics, Sultan ul Uloom College of Pharmacy, Banjara Hills, Hyderabad, Telangana, India Abstract Pharmaceutical calculations form the mathematical foundation of medication preparation, dispensing, and administration. Basic mathematical principles essential to pharmacy practice include measurement systems (metric, apothecary, household), unit conversions, ratio expressions, proportions, and alligation calculations that ensure accurate medication processing. Dosage calculations translate prescribed amounts into practical administration instructions, incorporating body weight and surface area considerations for pediatric and specialized populations, while accounting for creatinine clearance in renally eliminated medications. Compounding calculations support formulation development through percentage strength determinations, dilution ratios, molecular weight conversions, and accurate measurement of active and inactive ingredients to create customized medications. Concentration and dilution calculations enable pharmacists to prepare solutions of specified strengths, adjust existing concentrations, and perform isotonicity calculations ensuring physiological compatibility of parenteral preparations. These mathematical skills directly impact patient safety by preventing medication errors, enabling accurate dosing across diverse patient populations, and supporting the precise preparation of both routine and specialized pharmaceutical products. Keywords: Dosage Determination; Mathematical Accuracy; Measurement Conversion; Formulation; Preparation; Solution Concentration VIEW PDF